Enhancing interlayer bonding and fibre dispersion of fibre-reinforced polyether-ether-ketone composites prepared by online mixing extrusion through screw configuration optimisation - Siwei Lu; Yunze Wang; Beining Zhang; Jincang Bai; Chuncheng Yang; Yi Cao; Changning Sun; Dichen Li (Virtual and Physical Prototyping)
Material extrusion is currently the primary method for manufacturing fibre-reinforced polymer composites. However, its limitations in extrusion force and material selection restrict its broader application. In this study, a screw-based online mixing extrusion system was developed for carbon fibre-reinforced polyether-ether-ketone composites. The extrusion screw design was optimised using numerical simulation to enhance the mechanical properties of the printed parts. Simulation results indicated that the length of the metering section and the pitch have the greatest impact on extrusion pressure, while pin diameter and height significantly affect the mixing quality. The optimised screw with pins led to a 34% increase in extrusion pressure and a 73% enhancement in mixing degree, compared to that of the initial screw. Mechanical testing revealed that composite specimens produced with the optimised pin screw exhibited 27%, 36%, and 63% improvements in tensile strength, flexural strength, and interlayer shear strength, respectively, over those produced with the initial screw. Microscopic analysis showed that the enhanced performance was attributed to better interlayer bonding and improved fibre dispersion. This study presents a new paradigm for screw configuration design for screw extrusion-based 3D printing systems.